IntelliCane (Smartcane) / Nur Athirah Ibrahim … [et al.] - Ibrahim, Nur Athirah; Md Nuar, Mas Hidayu; Muhammad Zakir, Qasrina Batrisyia; Ali Othman, Adilah; Raub, Siti Nuraisyah; Juhari, Joeaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
SmartWay aims to create a future where individuals with disabilities can lead better lives through our advanced technological products. Our company has developed a product called "Intellicane" to assist blind people. "Intellicane" is a smart cane equipped with features such as obstacle recognition, fall detection, and navigation. Furthermore, our company recognizes that existing smart canes have extremely basic features. Therefore, to make our smart cane unique, we have added features like customizable settings that allow users to personalize their cane based on environmental conditions and the ability to easily connect "Intellicane" to smartphones and hearing aids if needed. In terms of novelty, we have incorporated an Emergency Alert System feature that will notify the user's family in case of an emergency. With our advanced "Intellicane," we believe we have a great chance of receiving positive feedback and achieving significant success from people with disabilities. We believe that our "Intellicane" product can help blind people walk more easily, despite any barriers or limitations, enabling them to move freely like sighted people. We have been testing our product on blind individuals for the past three months, and the results indicate that there are no issues. As a result, we are moving forward with releasing our product to the wider public. In conclusion, we hope that by utilizing our "Intellicane," our product will ensure that blind people can travel safely to their destinations.